PENGARUH LATIHAN EL RONDO TERHADAP KETERAMPILAN PASSING BAWAH SEPAK BOLA - Makhrus, M; Anwar, Khoirul; Handayani, Heni Yuli (Fakultas Ilmu Keolahragaan Unimed, 2024)
This study aims to determine the effect of El Rondo training on passing skills under football. The population in this study were 20 players U 12-15 at the Prabu Bhayangkara Bangkalan Football School. The experimental study used a one group pretest-posttest design with a total sampling technique, in which the entire population was sampled. Based on the research obtained, the results of the pretest = 15.00 in the less category and the posttest = 21.00 in the good category with a difference of 5.4. The statistical analysis used in this study is the t test. As for the results of the t test calculation results between the initial test and the final test there is a significant effect. The results of the calculations state that the value of tcount = 16.119> ttable = 1.699 with a level of ð›¼= 0.05 then ð»ð‘œ is rejected and ð»ð‘Ž is accepted meaning that there is a significant effect of El Rondo Training on Football Passing Skills. So it can be concluded that there is an influence of El Rondo training on passing accuracy in soccer games for Prabu Bhayangkara Bangkalan players